Community social capital and inequality in depressive symptoms among older Japanese adults: A multilevel study. (July 2018) - Haseda, Maho; Kondo, Naoki; Takagi, Daisuke; Kondo, Katsunori
Abstract: Although studies have suggested that community social capital contributes to narrow income-based inequality in depression, the impacts may depend on its components. Our multilevel cross-sectional analysis of data from 42, 208 men and 45, 448 women aged 65 years or older living in 565 school districts in Japan found that higher community-level civic participation (i.e., average levels of group participation in the community) was positively associated with the prevalence of depressive symptoms among the low-income groups, independent of individual levels of group participation. Two other social capital components (cohesion and reciprocity) did not significantly alter the association between income and depressive symptoms. Highlights: Community social capital might be protective towards depression in older adults. Community civic participation may enlarge the income-based gap in depression. Considering bright and dark sides of social capital is necessary for intervention.